2018
DOI: 10.1007/s11605-018-3809-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcomes in 394 Pancreatic Cancer Resections: the Impact of Enhanced Recovery Pathway

Abstract: CTRI/2015/01/005393 ( www.ctri.nic.in ).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Compliance with enhanced recovery after surgery (ERAS) elements has been favorably associated with reduced morbidity and length of stay and cost with no impact on readmission across surgical specialties. [108109110] Despite these positive results, evidence regarding ERAS in patients undergoing CRS-HIPEC procedures is lacking. The feasibility and benefits of ERAS in patients undergoing CRS-HIPEC were evaluated retrospectively before and after ERAS protocol and it was observed that the ERAS pathway was associated with significant reduction in the length of stay and early gastrointestinal recovery with no difference in morbidity and mortality.…”
Section: Enhanced Recovery After Surgery and Crs-hipecmentioning
confidence: 99%
“…Compliance with enhanced recovery after surgery (ERAS) elements has been favorably associated with reduced morbidity and length of stay and cost with no impact on readmission across surgical specialties. [108109110] Despite these positive results, evidence regarding ERAS in patients undergoing CRS-HIPEC procedures is lacking. The feasibility and benefits of ERAS in patients undergoing CRS-HIPEC were evaluated retrospectively before and after ERAS protocol and it was observed that the ERAS pathway was associated with significant reduction in the length of stay and early gastrointestinal recovery with no difference in morbidity and mortality.…”
Section: Enhanced Recovery After Surgery and Crs-hipecmentioning
confidence: 99%
“…In consideration of the relevant risk of postoperative complications and the poor survival, it has generally been accepted that for PDAC patients with metastatic disease, resection of the primary tumor or metastatic lesions is contraindicated. However, with the rapid development of new surgical techniques, more precise and minimally invasive operations, and better perioperative care, morbidity and mortality of pancreatic surgery has decreased in experienced centers 3,6 . New chemotherapeutic regimens also significantly prolong the survival of PDAC patients with metastatic tumors 7,8 .…”
mentioning
confidence: 99%
“…In similar side, the study of Enhanced recovery after surgery in gastrointestinal surgery done by Gao, et al [25] study reported that the ERAS protocols were associated with mild post-operative complications in study group compared with the control group. In addition, Agarwal, et al [26] that the majority of study group had lesser complications than control group. From the perspective of the researcher, application of Enhanced Recovery Programmed reduced complications due to early remove of urinary catheter, early mobilization, diet and performing exercise as breathing, coughing and ankle exercise.…”
Section: Discussionmentioning
confidence: 98%